Temperature-sensitive chlorophyll degradation uncouples degreening from other ripening traits and guides postharvest quality improvement in kiwifruit - Ameer Hamza Hafeez; Zheng Zhang; Ang Li; Zhebin Zeng; Yan Chen; Tiantian Li; Xiaomei Ji; Yi Wang; Zhongyan Wang; Yunjiang Cheng; Hamza Sohail; Di Feng; et al. (Postharvest Biology and Technology, 2026)

Cajaninstilbene acid induced apoptosis and cell cycle arrest in glioblastoma multiforme through mitochondrial ROS–mediated MAPK pathways - Yong-Ang Li; Tian-Zeng Bian; Hong Li; Jia-Wen Li; Liu-Tao Ma; Hao-Di Wu; Shuai Chen; Jia-Yi Chen; Hao Zeng; You-Bing Mao; Peng Wang; Qi Qiao (Food and Chemical Toxicology, 2026)

Tailored self-assembled molecule for efficient charge extraction and enhanced crystallization in wide-bandgap perovskite solar cells - Haojun Hu; Xianglang Sun; Xuke Yang; Zongbao Li; Peiyan Zhang; Xinyu Yu; Shi'ang Li; Zifan Lin; Dayu Liu; Ziyang He; Chuyun Deng; Longhui Zeng; et al. (Chemical Engineering Journal, 2026)

Evaluation of Natural Breasts and Post-Augmentation Breasts with Silicone Implants Using Subject-Specific Finite Element Modeling - Yuwei Zhang; Hailin Zhang; Jingqi Hu; Yiwen Jiang; Fuling Zheng; Ang Zeng; Xiao Long; Xiaojun Wang (Annals of Biomedical Engineering, 2026)

Chlorine dioxide fumigation induces transcriptomic and metabolomic reprogramming enhancing resistance to soft rot in kiwifruit - Ang Li; Shuang Luo; Di Feng; Xiaoya Chen; Zhidan Zhao; Tiantian Li; Yunhe Meng; Xiaoqin Yang; Yunjiang Cheng; Yunliu Zeng (Postharvest Biology and Technology, 2026)

A laser with instability reaching 4 × 10 - 17 based on a 10-cm-long silicon cavity at sub-5-K temperatures - Zhi-Ang Chen; Hao-Ran Zeng; Wen-Wei Wang; Han Zhang; Run-Qi Lei; Jian-Zhang Li; Cai-Yin Pang; She-Song Huang; Xibo Zhang (Science Bulletin, 2025)

Impact of per- and polyfluoroalkyl substances exposure on renal dysfunction: Integrating epidemiological evidence with mechanistic insights - Weitao Su; Ziwen An; Yayuan Mei; Zhenzhen Tan; Zexuan Jiang; Xiuli Zeng; Zhiqiang Dong; Ming Yang; Jingtao Wu; Huicai Guo; Ang Li (Environmental Pollution, 2025)

Impact of C-8 hydroxylation and C-7 methylglucosylation of dihydroquercetin on glucose metabolism in diabetic zebrafish larvae - Yong Cheng; Beijun Ang; Dandan Ma; Zhiwei Li; Fengxian Guo; Zhaojun Wang; Qiuming Chen; Maomao Zeng; Jie Chen; Benu Adhikari; Liduan Yin; Tong Wang; et al. (Food Bioscience, 2025)

The PpAHL17-PpHYH module is involved in light-independent anthocyanin accumulation in fruit peel of Prunus persica - Xiaoyu Zhang; Shihang Sun; Xin Liu; Junren Meng; Mingzhu Yuan; Ang Li; Wenyi Duan; Lei Pan; Zhiqiang Wang; Wenfang Zeng; Liang Niu (Plant Cell Reports, 2025)

Photothermal halloysite nanotube hybrids with CoO/carbon layers for enhanced pollutant degradation and solar-powered water purification - Yifang Zhang; Hongyao Zhao; Jiayi Zhou; Yanyun Wang; Yangping Zhang; Jialing Shen; Danhong Shang; Feng Zeng; Jianming Pan; Yiyan Song; Fu Yang; Edison Huixiang Ang (Desalination, 2025)

Hydroxylation of dihydromyricetin via Beauveria bassiana fermentation enhances its efficacy in improving insulin signaling: Insights into inflammation, oxidative stress, and endoplasmic reticulum stress - Yong Cheng; Junhao Wu; Yueqing Gao; Beijun Ang; Liduan Yin; Tong Wang; Qiuming Chen; Zhaojun Wang; Maomao Zeng; Jie Chen; Zhiyong He; Fengfeng Wu (Food Research International, 2025)

Enhanced ultrasound-assisted controllable growth assembly of MoS2/Fe3O4 materials for piezoelectric Fenton reaction degradation of sildenafil - Zi-ang Jia; Qing-rui Zeng; Jin-ping Cheng (Environmental Pollution, 2025)

Tissue accumulation and hepatotoxicity of 8:2 chlorinated polyfluoroalkyl ether sulfonate: A multi-omics analysis deciphering hepatic amino acid metabolic dysregulation in mice - Zhenzhen Tan; Ziwen An; Junli Lv; Fang Xiao; Longfei Li; Jing Li; Wenjing Duan; Mingmei Guo; Xiuli Zeng; Yi Liu; Ang Li; Huicai Guo (Journal of Hazardous Materials, 2025)

Legacy and alternative per- and polyfluoroalkyl substances spatiotemporal distribution in China: Human exposure, environmental media, and risk assessment - Jing Li; Wenjing Duan; Ziwen An; Zexuan Jiang; Longfei Li; Mingmei Guo; Zhenzhen Tan; Xiuli Zeng; Xuehui Liu; Yi Liu; Ang Li; Huicai Guo (Journal of Hazardous Materials, 2024)

Physical properties and anisotropy of sandstone during freeze-thaw cycle under unidirectional constraint - Tantan Zhu; Huanhuan Zhu; Ang Li; Xilei Zong; Bin Zeng; Xin He (Cold Regions Science and Technology, 2024)

The MYB transcription factor PpMYB5 regulates Pp4CL1/Pp4CL2 expression to promote lignin biosynthesis of fruit russeting in the flat nectarine - Yule Miao; Wenyi Duan; Ang Li; Mingzhu Yuan; Junren Meng; Hongmei Wang; Lei Pan; Shihang Sun; Guochao Cui; Caiyun Shi; Liang Niu; Wenfang Zeng (Plant Cell Reports, 2024)

High-intensity exercise training in large yellow croaker is a compromise between disease resistance and fish welfare - Junjia Zeng; Ang Qu; Yacheng Deng; Pengxin Jiang; Ji Zhao; Jiaying Wang; Yue Liu; Wei Liu; Qiaozhen Ke; Fei Pu; Yaxian Li; Peng Xu (Aquaculture, 2024)

Associations between co-exposure to per- and polyfluoroalkyl substances and organophosphate esters and erythrogram in Chinese adults - Ziwen An; Yanbing Li; Jing Li; Zexuan Jiang; Wenjing Duan; Mingmei Guo; Yiming Zhu; Xiuli Zeng; Linfeng Wang; Yi Liu; Ang Li; Huicai Guo; et al. (Chemosphere, 2024)

Non-destructive prediction of ready-to-eat kiwifruit firmness based on Fourier transform near-infrared spectroscopy - Gang Ding; Ke Jin; Xiaoya Chen; Ang Li; Zhiqiang Guo; Yunliu Zeng (Postharvest Biology and Technology, 2024)

Enhancing physicochemical, antimicrobial, and release properties of fish skin gelatin films using dual-layer nanoparticles loaded with tea polyphenols/kojic acid for air-dried chicken preservation - Ang Zhang; Xiankang Fan; Xiaoqun Zeng; Jue Xu; Changyu Zhou; Qiang Xia; Yangying Sun; Zhen Wu; Daodong Pan (Food Hydrocolloids, 2024)

Development and evaluation of a haplotype reference panel of Zhikong scallop (Chlamys farreri) for genotype imputation - Mingyi Sui; Zhi Liu; Xiaowen Huang; Zujing Yang; Haitao Yu; Chang Cui; Yuqing Hu; Xuefeng Wang; Xiaojing Shen; Qianqian Mu; Mingxuan Teng; Ang Zhao; et al. (Aquaculture, 2024)

Deep learning to obtain high-throughput morphological phenotypes and its genetic correlation with swimming performance in juvenile large yellow croaker - Junjia Zeng; Miaosheng Feng; Yacheng Deng; Pengxin Jiang; Yinlin Bai; Jiaying Wang; Ang Qu; Wei Liu; Zhou Jiang; Qian He; Zhijun Wang; Peng Xu (Aquaculture, 2024)

Insights into the fermentation potential of pollen: Manufacturing, composition, health benefits, and applications in food production - Yong Cheng; Beijun Ang; Chaoyi Xue; Zhenyu Wang; Liduan Yin; Tong Wang; Qiuming Chen; Zhaojun Wang; Maomao Zeng; Wei Zhang; Jie Chen; Zhiyong He (Trends in Food Science & Technology, 2024)

A novel 1T-2H MoS2/NaBi(MoO4)2 alternating-phase piezoelectric composites for high-efficient ultrasound-drived piezoelectric catalytic removal of Sildenafil - Qing-rui Zeng; Zi-ang Jia; Xu Liu; Jin-ping Cheng (Process Safety and Environmental Protection, 2023)

Sensitivity and control efficacy of a novel complex III inhibitor pyribencarb against Sclerotinia sclerotiorum - Ang Li; Hongjie Liang; Xinyi Cui; Weixu Yang; Xin Zhou; Pengwen Zeng; Dingzhi Pang; Shenjv Xia; Hongying Shan; Ning Li; Jinli Li (Journal of Plant Diseases and Protection, 2023)

Differential physiological response of marine and freshwater microalgae to polystyrene microplastics - Hengtao Xu; Li’ang Li; Youji Wang; Kecheng Qiu; Siyang Chen; Jiangning Zeng; Ruijuan Liu; Qikun Yang; Wei Huang (Journal of Hazardous Materials, 2023)

Enhanced ultrasound-assisted pore-adjustable spherical imma-Fe3O4 catalytic-activated piezoelectric Fenton reaction for PDE-5i degradation - Zi-ang Jia; Qing-rui Zeng; Xun Zhang; Wei Feng (Journal of Environmental Chemical Engineering, 2023)

Integrated mRNA and miRNA expression analyses for Cryptocaryon irritans resistance in large yellow croaker (Larimichthys crocea) - Ang Qu; Yulin Bai; Jiaying Wang; Ji Zhao; Junjia Zeng; Yue Liu; Xintong Chen; Qiaozhen Ke; Pengxin Jiang; Xinyi Zhang; Xin Li; Peng Xu; et al. (Fish & Shellfish Immunology, 2023)

The Combination of Platelet Rich Plasma Gel, Human Umbilical Mesenchymal Stem Cells and Nanohydroxyapatite/polyamide 66 Promotes Angiogenesis and Bone Regeneration in Large Bone Defect - Wei Liu; Yong Huang; Daqian Liu; Teng Zeng; Jingzhe Wang; Ang Li; Dawei Wang; Xiaoyu Wang (Tissue Engineering and Regenerative Medicine, 2022)

Tissue-Specific Analysis of Alternative Splicing Events and Differential Isoform Expression in Large Yellow Croaker (Larimichthys crocea) After Cryptocaryon irritans Infection - Ang Qu; Yulin Bai; Xinyi Zhang; Junjia Zeng; Fei Pu; Linni Wu; Peng Xu; Tao Zhou (Marine Biotechnology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Deduction and exploration of the evolution and function of vertebrate GFPT family - Si-ang Wei; Ran Xu; Yu-yao Ji; Zhi-wen Ding; Yun-zeng Zou (Genes & Genomics, 2022)

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

Foetidibacter luteolus gen. nov., sp. nov., isolated from the rhizosphere of Salvia miltiorrhiza - Qian Pu; Guo-hong Zeng; Gui-wei Wang; Ling-er Lu; Ang Li; Xu-rui Cheng; Xue-ying Wang; Ou Li; Cong Sun; Xiu-fang Hu (Archives of Microbiology, 2021)

Dynamic evaluation and spatiotemporal evolution of China’s industrial water use efficiency considering undesirable output - Changfeng Shi; Xinyun Zeng; Qianwen Yu; Junyuan Shen; Ang Li (Environmental Science and Pollution Research, 2021)

The Application of Decellularized Adipose Tissue Promotes Wound Healing - Zenan Xia; Xiao Guo; Nanze Yu; Ang Zeng; Loubin Si; Fei Long; Wenchao Zhang; Xiaojun Wang; Lin Zhu; Zhifei Liu (Tissue Engineering and Regenerative Medicine, 2020)

Over-expression of the Arabidopsis formate dehydrogenase in chloroplasts enhances formaldehyde uptake and metabolism in transgenic tobacco leaves - Ru Wang; Zhidong Zeng; Hongxia Guo; Hao Tan; Ang Liu; Yan Zhao; Limei Chen (Planta, 2018)

Changes in soil organic carbon and total nitrogen stocks after conversion of meadow to cropland in Northeast China - Fan Ding; Ya-Lin Hu; Lu-Jun Li; Ang Li; Shengwei Shi; Pei-Yong Lian; De-Hui Zeng (Plant and Soil, 2013)

Isolation and characterization of polymorphic microsatellite markers in the fish Garra orientalis (oriental sucking barb) - Li-Wei Su; Zhi-Zhi Liu; Cong-Tao Wang; Zhen Zeng; Ang-Yu Liu; Wen-Qiao Tang; Jin-Quan Yang (Conservation Genetics Resources, 2013)